Mapping Tools for Flood Risk Rescue and Assistance Management. - Sortino-Barrionuevo, Juan Francisco; Castro Noblejas, Hugo; Mérida-Rodríguez, Matías Francisco (MDPI, 2024)
The assessment of vulnerability to the danger of flooding, with a focus on the need for rescue and assistance from the population, is still in an exploratory scientific phase. The main objective of this research is to propose a methodology based on the issues of rescue and assistance in the face of the risk of floods and to provide a tool for its management. A series of maps is presented, indicating those territorial elements that require rescue and surveillance in a prioritized manner in a visual and accessible way for public administration. Four methodological cartographic proposals have been designed as follows: (1) a map of territory sectors with special rescue needs (dependent population and/or buildings without shelter); a map of the impact on transportation infrastructure and vulnerable areas of buildings (2); a map of vulnerability to possible disorder and looting caused by flooding events (3); and a map of the increase in the cost of deployment for rescue and assistance systems (4). As an experimental zone to test the effectiveness of these proposals, a peri-urban area of the municipality of Málaga (Spain) is chosen, which has an extensive history of severe floods. The results confirm the applied and preventive nature of the tool, which can be incorporated into flood risk management plans and local flood risk action plans developed by public administrations. The main finding of the research is the technical advancement that comes with a precise understanding of vulnerability and its resulting issues for better flood risk management.
Keywords: Inundaciones - Prevención; GIS; Flood risk management; Relief; Vulnerability mapping; Network analysis; Local scale